Irrational use of the clinical laboratory exams by the assistance doctors - Cira Cecilia León Ramentol; Guillermo Rivero Fexas; Mavel López Machado; Isis Patricia Rodríguez Socarrás (Centro Provincial de Información de Ciencias Médicas, 2015)
Introduction: the diagnosis tests are tools to help for the clinical decision, so that their use is considered inappropriate when they result in scarce or null information for such a decision. The laboratory medicine based on evidence combines the clinical epidemiology, statistic and the social sciences with the classic and the molecular biochemistry, with the aim of improving the effectiveness and the efficiency of the laboratory exams.   Objective: to demonstrate the irrational use of the laboratory exams by the assistance doctors. Methods: was carried out A longitudinal and descriptive study of 174 236 laboratory determinations, of 40 424 patients, assisted in "Eduardo Agramante Piña" University Provincial Pediatric Hospital in Camagüey, from July to December, 2013.   Results: in the series the exams carried out by the out-patients department prevailed, among them the hematological exams; also, a high percentage of indications tests keep relationship with the clinic.    Conclusions: the appropriate use of the clinical and epidemiological method, avoids the inappropriate use of complementary exams, so, a wider interrelation between the assistance doctors and the laboratory staff is recommended.